Arystokracja jako "stan" legitymizujący absolutystyczny ustrój administracji Śląska w okresie po wojnie trzydziestoletniej (1648-1740) = Aristocracy as a "state" legitimating absolutist system of the Silesian administration during the Thirty Years War (1648-1740) - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Absolutist regime in Silesia in the period 1648-1740 "created" a group of beneficiaries, which in fact was the aristocracy. Of course, it was a kind of "round-trip" covenant and worked both sides. Individual of aristocracy perform best positions and functions of defining the model of public life and social, and even economic.
Keywords: arystokracja; Śląsk; absolutyzm; administracja; Wojna Trzydziestoletnia - 1618-1648 - przywódcy; Aristocracy; Silesia; Absolutism; administration; Thirty Years? War